The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.nano.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Protein corona composition does not accurately predict hematocompatibility of colloidal gold nanoparticles

Abstract: Proteins bound to nanoparticle surfaces are known to affect particle clearance by influencing immune cell uptake and distribution to the organs of the mononuclear phagocytic system. The composition of the protein corona has been described for several types of nanomaterials, but the role of the corona in nanoparticle biocompatibility is not well established. In this study we investigate the role of nanoparticle surface properties (PEGylation) and incubation times on the protein coronas of colloidal gold nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
140
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 38 publications
5
140
2
3
Order By: Relevance
“…It is quite challenging to precisely characterize the composition of a protein corona because of its complex and dynamic nature [49]. However simple SDS-PAGE gel electrophoresis of desorbed proteins from NP previously incubated in a culture medium supplemented with serum can give some interesting insights.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite challenging to precisely characterize the composition of a protein corona because of its complex and dynamic nature [49]. However simple SDS-PAGE gel electrophoresis of desorbed proteins from NP previously incubated in a culture medium supplemented with serum can give some interesting insights.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure creates a hydrodynamic radius around the surface of NPs, which is efficient in reducing the overall amount of serum adsorbed proteins, thus reducing macrophagedriven clearance, but does not affect their qualitative composition [148,149]. Furthermore, PEG plays a critical role in triggering inflammatory and immunogenic phenomena [51].…”
Section: Evading the Immune Systemmentioning
confidence: 99%
“…[57][58][59] Although often referred to as protein corona, also other molecules, such as lipids, can adhere to the NMs. 57,60 The effect of the corona on the distribution and biocompatibility of NMs is not well understood yet.…”
mentioning
confidence: 99%
“…Coating with polyethylene glycol (PEG) has been shown to enable escape from the MPS for a prolonged period of time, thereby increasing the half-life in blood. 86,87 Dobrovolskaia et al 60 reported recently that the molecular weight of PEG coating affected the total amount of protein binding. However, the types of proteins forming the protein corona were not influenced by …”
mentioning
confidence: 99%
See 1 more Smart Citation